The Emergence of Shia, Khawarij and Sunni Groups in Islam at the Time the Caliphate of Sayyidina Ali bin Abi Talib of the year 35-41 H / 656-661 AD in the Arabian Peninsula. - mohamad fajar setiyawan; sumardi sumardi; Kayan Swatika (History Education, University of Jember, 2020)
During the reign of Caliph Ali bin Abi Talib emerged three groups in Islam who would later continud to provide a complete picture of differences in Islam, both politically, ideologically, and culturally. The groups were the Syiah, the Khawarij and the Sunni. The formulation in this study are; 1) the background and process of the emergence of 3 groups in Islam namely Syiah, Khawarij and Sunni 35 - 41 H in the Arabian Peninsula, 2) how was the life developments of the 3 groups in Islam namely Syiah, Khawarij and Sunni years 35 - 41 H / 656-661 M in the Arabian Peninsula, and 3) how the impact of the emergence of Islam into 3 groups namely Syiah, Khawarij and Sunni 35 - 41 AH / in the Arabian Peninsula. This study uses the Political approach and Ibn Khaldun's Conflict theory. The results of this study are the existence of political interests and the emergence of power struggles between Muslims which ended in the form of firqah, the three political groups that emerged and had great influence were Syiah (pro-Ali), Khawarij (counter-Ali) and Sunni (some pro-Muawiyah, part pro-Ali and partially neutral). The impact of the emergence of these three groups in Islam finally formed differences and separations between groups with other groups, both ideologically, politically and culturally.